Motor capacity of higher members in visually disabled goalball practitioners (Research, Society and Development, 2020)
Objective: To evaluate the strength of upper limbs in visually impaired people who practice a goalball project. Methodology: This research is a cross-sectional, descriptive study with quantitative analysis. Participated in the research 10 students from an educational institution that serves people with visual impairments, practitioners of the sport of Goalball. As for the research instruments and procedures, the participants were submitted to two evaluation protocols: 1) Upper limb strength test (Medicine Ball pitch) and 2) Upper limb strength test (dynamometry). Results: In general, the results found by the manual dynamometry test revealed low levels of strength, both for men 68.7 kg (± 17.7) and for women 47.1 kg (± 12.7), which evidenced a physical condition considered precarious for this ability. Although for the Medicine Ball pitch test the results were more satisfactory, it was still found that the participants denoted a condition assessed as regular, with the values found being 2.82m (± 0.5) for women and 3.67m (± 0.8) for men. Conclusion: From the results, it was concluded that both the practice of physical activities and adequate strength work should be encouraged among visually impaired people, since insufficient exercise can compromise the functional capacities of individuals.